Taxonomy of mycotoxigenic fungi - Vankudoth, Koteswara Rao; Sivadevuni, Girisham; Reddy S. M. (Scientific Publisher, 2016)
Mycotoxins, toxic metabolites of molds elaborated during their colonization of foods and feeds, pose a threat to human and animal life. Molds are the diverse group of fungi, which grow in compatatively dry and warm environments, produce copious amount of spores and promote the elaboration of these mycotoxins. Mycotoxigenic fungi, which are unique their sporulating apparatus and exhibit wide variation in their morphology, poses a challenge in their identification. There are numerous examples of their misidentification leading to wrong conclusions. Precise information on taxonomy of these fungi is lacking. Therefore, this book fulfills the need of providing comprehensive information and keys helpful for the accurate identification of these moulds. The book also provides comprehensive account of morphology, mycotoxins produced and factors leading to the elaboration of mycotoxins. Information on their molecular detection, anamorphic and teleomorphic relationships is also included.